Experimental analysis of infectious passenger isolation system for aircraft - Darrah, Ian David (Kansas State University, 2018)
Limiting the spread of infectious airborne diseases and airborne pathogens is an important consideration in aircraft environmental control system design. However, when a passenger suspected of having a highly contagious disease or very dangerous disease is identified in flight, it is desirable to further isolate the individual from other passengers. A research project was conducted to explore an isolation system that can be stored in a small space and deployed in flight if needed. This device is referred to as an “Expedient Passenger Isolation System” abbreviated as ISOPASS. The ISOPASS is a portable, negative-pressure isolation system that can be installed over a section of seats quickly by a flight attendant during flight. A prototype proof of concept ISOPASS was evaluated in this study. Measurements were conducted in a full-scale, 11-row mock-up of a wide-body aircraft cabin, as well as a 5-row section of a narrow-body aircraft cabin. Heated mannequins to simulate the thermal load of passengers inside the cabin were seated in the mockup. Carbon dioxide was used as a tracer gas and was mixed with helium to maintain neutral buoyancy in air. The tracer gas was used to simulate airborne pathogen spread and was injected at the breathing level at a seat within the ISOPASS. Tests were conducted with and without the ISOPASS in place. Matched pairs were used to mitigate potential statistical problems. Matched pair tests were completed with gaspers turned on and off. Measurements were repeated three times for each gasper setting and for each ISOPASS condition. Concentration measurements were taken at the breathing level inside the ISOPASS at the seat next to the injection source; at the seat across the aisle adjacent to the ISOPASS; and at a seat far away from the ISOPASS near the front of the cabin. The with- and without-ISOPASS matched pair tests clearly show the ISOPASS prototype is highly effective at providing isolation in each aircraft cabin used in the study. Additionally, it was determined that the use of gaspers makes no measurable difference in the containment effectiveness of the ISOPASS.
Keywords: Aircraft; Isolation; Occupant health; Indoor environmental engineering; Environmental control systems